The effect of chlorella fortification on the quality of sago mocaf analogue rice - Farhan, Muhammad; Iriani, Dian; Syahrul, Syahrul; Sari, N Ira (Universitas Malikussaleh, 2024)
Analog rice is artificial rice shaped like rice which can be made from non-rice flour. This research aims to determine the effect of Chlorella fortification on the quality of sago mocaf analog rice and to find out the best formulation The method used in the study was an experiment with a non-factorial completely randomised design (CRD), with 4 treatment levels in the manufacturing of sago mocaf analog rice with different amount of Chlorella powder namely: 0 g (BA0), 1 g (BA1), 1.5 g (BA2) and 2 g (BA3). Based on the results, sago mocaf analogue rice-fortified Chlorella has a significant effect on appearance, aroma, taste, ash, protein, fat and carbohydrate content but has no significant effect on the texture and moisture content at the 95% confidence level. Based on the organoleptic test, the addition 1 g of Chlorella powder (BA1 treatment) in the manufacturing of sago mocaf analog rice was most preferred by consumer acceptance with the characteristics: complete appearance and greenish colour (8.71), neutral aroma/no Chlorella smell/typical sago aroma (8.73), good taste and a slight taste of fish flour (8.60), very hard texture and not easily broken (8.63); with 4.70% of water content, 1.42% of ash, 10.57% of protein, 4.54% of fat and 78.84% of carbohydrate. Sago mocaf analog rice fortified Chlorella produced meet the Indonesian National Standard.Keywords: Analog Rice; Chlorella; Fortification; Mocaf; Sago